PERBEDAAN KADAR INTERLEUKIN-1β DALAM CAIRAN SULKUS GINGIVA PADA AKTIVASI PIRANTI ORTODONTI CEKAT DENGAN LEPASAN - Kornialia Kornialia (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Orthodontic treatment with both fixed and removable appliances provides mechanical stress on the teeth which aims to move the teeth. Orthodontic pressure causes the release of inflammatory mediators such as interleukin-1β from the periodontal ligament and alveolar bone thereby stimulating bone resorption and IL-1β. The purpose of this study was to determine the difference in IL-1β levels before (0 hours), 5 minutes, 24 hours and 48 hours after mechanical stress was applied between fixed and removable orthodontic appliances. Methods: This type of research is analytic observational with a comparative cross sectional approach to the fixed device user group and the removable device group. IL- levels of each group were examined at those 4 times. The concentration of IL-1 was checked using ELISA. Results: The results showed that there were no statistically significant differences in IL-1 levels between fixed and removable orthodontic appliances at 0 hours (p=0.907), 5 minutes (p=0.085), 24 hours (p=0.491) and 48 hours. (p=0.814). There was a statistically insignificant difference between the fixed and removable groups (p=0.284). Both fixed and removable devices had a pattern of IL-1 concentrations that increased at 24 hours and decreased after 48 hours, the mean level of IL-1 in the fixed device group was higher than that in the removable device group at 5 minutes (1,176±1,041). pq/ml and 0.347±0.212 pq/ml) and 24 hours (1.897±3.227 pq/ml and 0.927±0.790 pq/ml). Conclusion: From the results of the study, it can be concluded that mechanical pressure from fixed and removable orthodontic appliances causes an acute inflammatory response which is characterized by an increase in IL-1β levels which peaked at 24 hours and decreased 48 hours after mechanical pressure was applied.